KARAKTERISTIK ART DECO DALAM KARYA FRANS JOHAN (Studi Kasus : Analisis Desain dan Signifikansi Budaya) - Aji Suryo Atmojo; Astria Melanira (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2024)
This study examines the characteristics of Art Deco in the works of Frans Johan, focusing on design analysis and cultural significance. Art Deco, known for its elegance, luxury, and modernity, influenced various artistic fields, including architecture, interior design, and visual arts during the early 20th century. Frans Johan, as one of the prominent figures in this style, integrated geometric patterns, bold colors, and ornamental details that reflect the spirit of the era. This research utilizes a qualitative approach, analyzing selected artworks through visual observation and literature review. The findings reveal the unique application of Art Deco elements in Johan's works, highlighting his contribution to the evolution of modern design. Furthermore, the study explores the cultural significance of his creations, revealing how they reflect social dynamics and aesthetic values of the time. This research contributes to a deeper understanding of Art Deco's impact on artistic development and cultural identity.